Analisis pengadaan obat antibiotik di Apotek Bio's Farma menggunakan metode analisis konsumsi - Linda Fauziah Ariyani; Vina Anasthasia Sagita; Putri Jihannisa (PHARMACIA, 2023)
Procurement of drugs in pharmaceutical installations is a process of providing drug needs in health centers, one of which is in pharmacies. The aim of this study is to classify antibiotic drugs at Bio's Farma Pharmacy by their investment value to see how much spending is spent according to drug procurement at Bio's Farma pharmacies and their usage. required. The method used is the consumption method with ABC analysis to determine the investment value of the antibiotic drug. The results obtained are that group A with the number of types of drugs as many as 2 antibiotics has an investment value of Rp. 433,500,000.- and the percentage is 50%. Category B group, the number of drugs is 2 antibiotics, which has an investment value of Rp. 99,302,000, - with a percentage of 20%. And for the category C group, the number of drugs is 5 antibiotics with an investment value of Rp. 81,750,000, - with a percentage of 20%.